Innovation strategies in the grammar teaching of English and its effectiveness during the third level educational process - Veliz Blacio, Jacqueline Jeaneen (RECIMUNDO, 2020)
Proficiency in English is a skill of increasing competitive importance for professional development; therefore effective learning in university preparation has a strategic character. The low level of mastery of this language at the national and regional level, constitutes an important indicator of the poor methodology and strategies applied in the Ecuadorian education system, in this context the present investigation of documentary type is intended to conduct a review of the various educational and evaluative strategies in learning this second language, assessing its usefulness, and thus contributing to the debate to reverse this situation.